EVALUASI SISTEM PENYIMPANAN ALAT KESEHATAN DI SALAH SATU PEDAGANG BESAR FARMASI (PBF) DI KOTA BANDUNG - Rahmawaty Adira (Sam Ratulangi University, 2023)
Medical devices are instruments, apparatus, machines, and/or implants that do not contain drugs that are used to prevent, diagnose, cure and alleviate disease, treat sick people, restore health to humans, and/or form structures and improve body functions whose distribution flow has been regulated in the Good Medical Devices Distribution Method. One aspect that needs attention in this Good Medical Devices Distribution Method is the medical device storage system. This study aims to evaluate the suitability of the medical device storage system at one of the Pharmaceutical Wholesalers in the city of Bandung with the existing regulations. The results of this study indicate that the medical device storage system at one of the Pharmaceutical Wholesalers in the city of Bandung is very compatible with the Good Medical Devices Distribution Method, even so there are several evaluations of overloaded medical device storage which are stored in the corridors of the medical device storage warehouse. Keywords: Storage, Medical Devices, CDAKB